Novel Immune Check-Point Regulators in Tolerance Maintenance - Guo, Yanxia; Wang, Adele Y. (Frontiers in Immunology, 2015)
The great success of anti-cytotoxic lymphocyte antigen 4 (CTLA4) and anti-programmed cell death protein 1 (PD1) in cancer treatment has encouraged more effort in harnessing the immune response through immunomodulatory molecules in various diseases. The immunoglobulin (Ig) super family comprises the majority of immunomodulatory molecules. Discovery of novel Ig super family members has brought novel insights into the function of different immune cells in tolerance maintenance. In this review, we discuss the function of newly-identified B7 family molecules B7-H4 and V-domain Ig Suppressor of T cell Activation (VISTA), and the butyrophilin/butyrophilin-like (BTN/BTNL) family members. We discuss the current stages of immunomodulatory molecules in clinical trials of organ transplantation. The potential of engaging the novel Ig superfamily members in tolerance maintenance is also discussed. We conclude with the challenges remaining to manipulate these molecules in the immune response.